Postoperative Monitoring of Free DIEP Flap in Breast Reconstruction with Near-Infrared Spectroscopy: Variables Affecting the Regional Oxygen Saturation - Salgarello, Marzia; Pagliara, Domenico; Rossi, Marco; Visconti, Giuseppe; Barone-Adesi, Liliana (Journal of Reconstructive Microsurgery, 2018)
Background The timing of surgical reexploration in microanastomotic thrombosis is directly related to the salvage rate of free flap. Near-infrared spectroscopy (NIRS) is a noninvasive technique, which allows a continuous bedside monitoring of flap oxygenation. The current literature is lacking in the assessment of variables able to modify the NIRS monitoring. The aim of this study is to identify patient and flap-related variables that can affect regional oxygen saturation (rSO2).Methods We retrospectively analyzed the data obtained from 45 consecutive patients undergoing breast reconstruction with deep inferior epigastric perforator (DIEP) flap. The monitoring device used is the Somanetics INVOS 5100C Cerebral/Somatic Oximeter (Covidien). Baseline measures of demographic–anthropometric variables (age, weight, height, body mass index [BMI]) and flap factors (flap size in grams, skin flap area in square centimeters, perforator number, and perforator size in millimeters) were collected from preoperative and intraoperative assessment. We investigated the linear correlation between mean rSO2 and BMI, flap size, skin flap area, perforator number, and perforator size.Results A positive linear correlation between rSO2 values and skin flap area, perforator number, and perforator size was found. A negative linear correlation between rSO2 values and BMI and flap size was found. All correlations are statistically significant. Despite the overall negative linear correlation between rSO2 values and flap size, we observed a bimodal trend: a positive relation up to 800 g, which is inverted above 800 g.Conclusion The NIRS is a reliable additional tool in free flap monitoring. A careful evaluation should be given to patients and surgery factors that can change the oximetry data.
Keywords: DIEP flap; NIRS monitoring; variables in NIRS monitoring